The use of edge computing-based internet of things big data in the design of power intelligent management and control platform. (5th March 2022) - Ju, Xin; Gou, Ruixin; Xiao, Yanli; Wang, Zheng; Liu, Shangke
The purpose of this research is to apply the Internet of Things (IoT) and big data technology to the power management and control platform, and improve the intelligent level of power management and control. Based on edge computing and cloud platform technology, this research designed a power intelligent management and control platform and a lightning positioning system based on the Internet of Things technology. Finally, taking the Shaanxi regional power grid as an example, the power consumption data of 8000 users was selected as the data source for cluster analysis. The results found that the power intelligent management and control platform can monitor power equipment online, realise intelligent analysis of multi-source data, and is better than traditional centralised algorithms in classification accuracy and platform running time, in the hope that its good management and control performance can be applied in practice.